U-Shaped Association of Aspect Ratio and Single Intracranial Aneurysm Rupture in Chinese Patients: A Cross-Sectional Study - Yin, Jia-He; Su, Shi-Xing; Zhang, Xin; Bi, Yi-Ming; Duan, Chuan-Zhi; Huang, Wei-mei; Wang, Xi-Long (Frontiers in Neurology, 2021)
BACKGROUND: Previous research linking aspect ratio to ruptured intracranial aneurysm (IA) have been controversial and limited by methodology. Thus, this study was performed to examine whether aspect ratio (AR) is independently associated to single IA rupture. METHODS: The present work was a cross-sectional study. The medical records of 1588 patients with single intracranial aneurysms diagnosed at the Guangzhou Zhujiang hospital between January 2010 to November 2017 were reviewed and analyzed. The interested independent variable and the outcome variable were AR and IA rupture respectively. Covariates included data of demographics, morphological parameters, lifestyle habits, clinical features and comorbidities. Univariable and multivariable binary logistic regression models and generalized additive models were used to evaluate the effects of AR on IA rupture risk. . RESULTS: Multivariable adjusted binary logistic regression indicated AR was not associated with rupture status (Odds ratio (OR)=1.00, 95%CI 0.98 to 1.03, per 0.1 change of AR). A U-shaped curve between AR and risk of aneurysmal rupture was obtained, whose inflection points were 1.99 and 3.42. The OR values and the confidence intervals on both sides of inflection point were 0.87(0.80 to 0.98) at the range of 1.08 to 1.99 of AR, 1.01 (0.98, 1.04) at the range of 1.99 to 3.42, and 1.03 (1.01 to 1.06) at the range of 3.42 to 4.08, respectively. The stronger association between AR and rupture risk was detected in current smoker, drinker, patients without willis variation, narrow neck, lower angle, lower value of SR. The opposite trend was seen in larger size of IA. CONCLUSION: The independent correlation between AS and IA presented a U shape. There is an interaction among morphological factors and lifestyle habits . KEYWORDS: aspect ratio, rupture of intracranial aneurysm, association, generalized additive model, subgroup analysis